Upaya-Upaya Indonesia Dalam Resolusi Konflik Papua - Aurelia Angelina Djeen (JURNAL SOSIO-KOMUNIKA, 2022)
Papua's domestic problems are often discussed in the UN General Assembly and have received a lot of criticism. Criticism came from Pacific Island countries, including the Solomon Islands, Vanuatu and Marshall Islands. These criticisms often mention human rights violations and Indonesia's injustice towards Papua. The problems in Papua are domestic problems that have  become  international problems. This is because other countries feel the need to take part in solving problems in Papua. In the UN General Assembly that contains Indonesia's criticism of Papua, the Government of Indonesia responds firmly that this problem is a domestic problem. Indonesia has also made various attempts to build conflict resolution in the Papua region. In addition to infrastructure development, the Papua conflict resolution discussed relates to the procurement of human rights representatives, the Papua Truth and Reconciliation Commission. Attempts to build a human rights court office are still being discussed. Attempts to expand the Papua region. In addition, attempts to  form  local  political  parties  are  still  being  considered  due  to  obstacles.  This research uses the concept of conflict and conflict resolution by Galtung. And this research uses development theory which  is analyzed  using  qualitative  analytical techniques.